2020
DOI: 10.5796/electrochemistry.19-00065
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Potential Oscillation during Electrolysis of Water in Acidic Solutions

Abstract: We have previously reported that the hydrogen evolution reaction (HER) in acidic water electrolysis shows a potential oscillation with amplitude of about 1 V. The oscillation, named HER oscillation, is accompanied with a periodic change in the evolution rate of hydrogen bubbles, i.e., hydrogen bubbles evolve more vigorously at low potentials than at high potentials, which has led us to propose a mechanism for HER oscillation (J. Electroanal. Chem., 713, 39 (2014)). In order to obtain a deeper insight into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These are typical features of ERDC-type oscillations. [22][23][24] Through these studies, we concluded that the potential oscillation of oscillation II acted under the ERDC mechanism. Specifically, the potential decrease is attributed to the diffusion limitation of the electroactive species (i.e., nitrate ions), and the potential increase is induced by enhanced convection due to bubble evolution.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These are typical features of ERDC-type oscillations. [22][23][24] Through these studies, we concluded that the potential oscillation of oscillation II acted under the ERDC mechanism. Specifically, the potential decrease is attributed to the diffusion limitation of the electroactive species (i.e., nitrate ions), and the potential increase is induced by enhanced convection due to bubble evolution.…”
Section: Discussionmentioning
confidence: 84%
“…There are other types of oscillations that show different characteristics, namely, strictly potentiostatic, capacitance-mediated positive differential resistance (C-PDR), 17,18 S-shaped NDR (S-NDR), 19 coupled N-NDR (CN-NDR), 20,21 and electrochemical reactions and diffusion-convection (ERDC). [22][23][24] The last two are associated with vigorous bubble evolution from the electrode surface because forced convection, which is essential for oscillations, is induced by bubble evolution. Depending on the type of oscillation, either current or potential oscillations may appear, or both.…”
mentioning
confidence: 99%
“…Specifically, these are strictly (or truly) potentiostatic, 29,32 S-shaped NDR, 33 capacitance-mediated positive differential resistance, 34,35 electrochemical reactions, and diffusion--convection types. [36][37][38] Note that these mechanisms are not responsible for the corrosion potential oscillation because an N-NDR characteristic is essential for the oscillation as shown below.…”
mentioning
confidence: 99%
“…Other than these typical oscillators, there are several distinct types, namely, strictly potentiostatic, S-shaped NDR (S-NDR), 20 coupled N-NDR (CN-NDR), 18,19 capacitance-mediated positive differential resistance (C-PDR), 21,22 and electrochemical reactions and diffusion-convection (ERDC) [23][24][25] types. When determining the type of oscillation, electrochemical impedance spectroscopy (EIS) measurements are highly useful because EIS can show whether and how an NDR is involved in the system of interest.…”
mentioning
confidence: 99%
“…Interestingly, not only the HPRR but also the HER shows oscillations because of the increase in pH s . 25,31,32 The suppression of reactions is partially due to an increase in the solution pH. For example, the pH of 0.1 M H 2 SO 4 solution slightly increases by adding Na 2 SO 4 or K 2 SO 4 , resulting in the suppression of the HER (i.e., a decrease in the HER current).…”
mentioning
confidence: 99%